Investing in Public Investment : An Index of Public Investment Efficiency - Mills, Zac (IMF Working Papers; Working Paper ;, 2011)
This paper introduces a new index that captures the institutional environment underpinning public investment management across four different stages: project appraisal, selection, implementation, and evaluation. Covering 71 countries, including 40 low-income countries, the index allows for benchmarking across regions and country groups and for nuanced policy-relevant analysis and identification of specific areas where reform efforts could be prioritized. Potential research venues are outlined.